Ramadan fasting in people with type 1 diabetes during COVID-19 pandemic: The DaR Global survey. (February 2021) - Hassanein, Mohamed; Alamoudi, Reem M.; Kallash, Majd-Aldeen; Aljohani, Naji J.; Alfadhli, Eman M.; Tony, Lobna El; Khogeer, Ghofran S.; Alfadhly, Abdulaziz F.; Khater, Ahmed ElMamoon; Ahmedani, Muhammad Yakoob; Buyukbese, Mehmet Akif; Shaltout, Inass; et al.
Abstract: Objectives: The DaR Global survey was conducted to determine the impact of the COVID-19 pandemic on the intentions to fast and the outcomes of fasting in <18 years versus ≥18 years age groups with type 1 diabetes mellitus (T1DM). Methods: Muslim people with T1DM were surveyed in 13 countries between June and August 2020, shortly after the end of Ramadan (23rd April–23rd May 2020) using a simple questionnaire. Results: 71.1% of muslims with T1DM fasted during Ramadan. Concerns about COVID-19 were higher in individuals ≥18 years (p = 0.002). The number of participants who decided not to fast plus those who received Ramadan-focused education were significantly higher in the ≥18-year group (p < 0.05). Hypoglycemia (60.7%) as well as hyperglycemia (44.8%) was major complications of fasting during Ramadan in both groups irrespective of age. Conclusion: COVID-19 pandemic had minor impact on the decision to fast Ramadan in T1DM cohort. This was higher in the age group of ≥18 years compared to those <18 years group. Only regional differences were noted for fasting attitude and behavior among T1DM groups. This survey highlights the need for Ramadan focused diabetes education to improve glucose control and prevent complications during fasting.